Mobile or Web-Based Intervention for Smoking Cessation - Ifa Nofalia; Suhendra Agung Wibowo (Babali Health, 2020)
Introduction: Smoking is the most preventable cause of illness and premature death worldwide. Because of the danger of smoking, smoker must try to quit smoking. The purpose of this research was to determine the effect of mobile or web-based intervention on smoking cessation program. Methods: This study was used systematic review with literature search using online reference databases such as ProQuest, ScienceDirect and SCOPUS. The keywords that used in this research was mobile intervention, phone intervention, apps intervention, web-based intervention, and smoking cessation. This study included randomized controlled trial studies with mobile or web-based intervention for smoking cessation program. Results: Twenty-five RCTs showed intervention groups with mobile or web-based had better affect to stop smoking than control groups or comparison groups. Conclusion: Smoking cessation is also influenced by the focusing of mobile or web-based intervention provided. Thus, providing information about the strengths and the effect of therapy is important.